2014
DOI: 10.1111/maps.12344
|View full text |Cite
|
Sign up to set email alerts
|

The Ardón L6 ordinary chondrite: A long‐hidden Spanish meteorite fall

Abstract: Abstract-We report and describe an L6 ordinary chondrite fall that occurred in Ard on, Le on province, Spain (longitude 5.5605°W, latitude 42.4364°N) on July 9th, 1931. The 5.5 g single stone was kept hidden for 83 yr by Rosa Gonz alez P erez, at the time an 11 yr old who had observed the fall and had recovered the meteorite. According to various newspaper reports, the event was widely observed in Northern Spain. Ard on is a very well-preserved, fresh, strongly metamorphosed (petrologic type 6), and weakly sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…This fireball is called SPMN081011_194759. The computed trajectory and velocity when compared with the relative abundances of the main rocky elements provides unprecedented information on differential ablation along the meteor path (Trigo-Rodríguez et al 2003) and clearly supports the idea that ablation of different chemical elements occurs at different locations along the meteor column. The spectrum of this fireball is compared with spectra produced by five fainter singlestation October Draconid fireballs which were also imaged during the maximum peak of the 2011 outburst.…”
Section: Introductionsupporting
confidence: 54%
“…This fireball is called SPMN081011_194759. The computed trajectory and velocity when compared with the relative abundances of the main rocky elements provides unprecedented information on differential ablation along the meteor path (Trigo-Rodríguez et al 2003) and clearly supports the idea that ablation of different chemical elements occurs at different locations along the meteor column. The spectrum of this fireball is compared with spectra produced by five fainter singlestation October Draconid fireballs which were also imaged during the maximum peak of the 2011 outburst.…”
Section: Introductionsupporting
confidence: 54%
“…In reality, any of the criteria outlined in Jopek and Williams (2013) could be used, but the Southworth and Hawkins criterion has been used several times before in this context (e.g. Trigo-Rodríguez et al, 2007;Madiedo et al, 2013Madiedo et al, , 2014.…”
Section: Orbital Clues On the Origin Of Annama: Is There A Link With mentioning
confidence: 99%
“…The possibility that meteorite-dropping bolide complexes associated with asteroids could exist was first proposed by Halliday (1987). Trigo-Rodríguez et al (2007 also found dynamic associations between large meteoroids and Near Earth Objects (NEOs). Many asteroids are rubble piles and so probably do not require a collision in order to be disrupted.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations